Comparison of two routinely used mouthwashes for plaque control among young adults: An observational study - Pratibha Singh; Sasi Krishna Busani; Rajnish K Verma; Chinmayi Prabhakar; Ravi Kadur Sundar Raj; Alok Dubey (Journal of Pharmacy and Bioallied Sciences, 2024)
Background: The most common and convenient technique to provide antiplaque medicines is through mouth rinses, which have the advantage of accessing places that are difficult for a toothbrush to clean. Chlorhexidine and Listerine mouthwashes were tested for their effectiveness when used in addition to routine teeth cleaning techniques. However, the studies assessing the antibacterial effects of these among young adults are diversified and limited. Materials and Methods: This comparative study was conducted among 240 schoolchildren. The participants were separated into three groups: A, B, and C. The research was conducted at two intervals of time, before therapy and during treatment period. The plaque was assessed through the plaque index (Turesky modification of Quigley-Hein plaque index (1970)). After a month, individuals had oral examination and were assessed. Results: Following the first week, a comparison of plaque scores was made between the three groups. Plaque score is lower in group C and group B than in group A in the succeeding second, third, and fourth weeks, but Tukey's test results suggest that group C has a larger decrease in plaque than group B. Conclusion: According to this study, as compared to a placebo mouthwash, both a mouthwash containing 0.2% chlorhexidine and one containing phenol dramatically reduced plaque development and gingival irritation.